2015
DOI: 10.1111/jan.12641
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of older and middle‐aged adults' perception and attitudes towards dementia and dementia risk reduction

Abstract: These findings can be used to develop effective and personalized interventions that increase motivators and reduce barriers by tailoring interventions to individual's dementia risk reduction literacy and motivations to change behaviours. Greater public-health promotion and education about risk and protective factors for dementia are also necessary to increase dementia health literacy and to reduce overall dementia prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
96
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(111 citation statements)
references
References 35 publications
8
96
0
Order By: Relevance
“…In this context, health promotion initiatives and the popular press strongly advocate that middle-aged adults should structure their lifestyle around a dementia-prevention regime that infiltrates the most routine dimensions of daily life, dictating appropriate food choices, behavioral practices, and mental activities (O'Connor and Joffe, 2015). The prominence afforded to these ideas means that among the general lay population, there is now high awareness regarding the supposedly protective effects of crossword puzzles, dietary supplements, and social interaction (Friedman et al, 2009;Kim et al, 2015;O'Connor and Joffe, 2015).…”
Section: Neuro-enhancement In Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, health promotion initiatives and the popular press strongly advocate that middle-aged adults should structure their lifestyle around a dementia-prevention regime that infiltrates the most routine dimensions of daily life, dictating appropriate food choices, behavioral practices, and mental activities (O'Connor and Joffe, 2015). The prominence afforded to these ideas means that among the general lay population, there is now high awareness regarding the supposedly protective effects of crossword puzzles, dietary supplements, and social interaction (Friedman et al, 2009;Kim et al, 2015;O'Connor and Joffe, 2015).…”
Section: Neuro-enhancement In Agingmentioning
confidence: 99%
“…However, they retain a grip on the public imagination due to the fear that dementia commands in contemporary culture. Research shows that aging is often accompanied by high levels of dread about future cognitive decline (Cutler and Hodgson, 1996;Corner and Bond, 2004;Kim et al, 2015). A 2014 US poll conducted by the Alzheimer's Association identified Alzheimer's disease as the public's most feared illness, and the recent increase in dementia prevalence is framed in hyperbolic terms of an "epidemic, " "tsunami, " or "time-bomb" (Peel, Buckley et al, 2015).…”
Section: Neuro-enhancement In Agingmentioning
confidence: 99%
“…The authors found that there was a lack of knowledge about dementia risk factors [18]. The lack of knowledge on dementia risk factors was also seen to be the main barrier for behavioral and lifestyle changes [18]. If risk models incorporating modifiable risk factors for dementia are used, then there needs to be greater promotion and education around dementia risk factors so that at-risk individuals are motivated to reduce their risk of future dementia.…”
Section: Patient and Public Perceptions Of Dementia Risk Reductionmentioning
confidence: 99%
“…There has been a recent attempt to assess perceptions of dementia risk reduction in older and middle-aged adults in a focus group study [18]. The authors found that there was a lack of knowledge about dementia risk factors [18]. The lack of knowledge on dementia risk factors was also seen to be the main barrier for behavioral and lifestyle changes [18].…”
Section: Patient and Public Perceptions Of Dementia Risk Reductionmentioning
confidence: 99%
See 1 more Smart Citation